Creatively teach the common core literacy standards with technology grades 6-12 - Tucker, Catlin R. (Thousand Oaks, California Corwin, 2016)
Tucker helps make the transition to the Common Core easier, by introducing to the technology and devices that will help you-- and your students-- create a more meaningful and resonant learning experience.
The heart of the Common Core: points of emphasis in the literacy standards -- Transforming low-tech classrooms with BYOD and mobile devices -- The reading standards -- Argumentative writing -- Informative writing -- Narrative writing -- Rethinking research -- Language -- Speaking and listening -- Charging ahead in the face of change -- Appendix: Tools and strategies for developing skills identified in the Common Core Anchor Standards.
Includes bibliographical references (pages 200-202) and index.
Includes List of Live Links (pages x-xvi)
Keywords: Language arts (Middle school); Language arts (Secondary); Language arts (Middle school) -- Computer-assisted instruction; Language arts (Secondary) -- Computer-assisted instruction; Common Core State Standards (Education); Educational technology